A Note on Best Proximity Point Theorems under Weak P-Property - Angel Almeida; Erdal Karapınar; Kishin Sadarangani (Abstract and Applied Analysis)
In the very recent paper of Akbar and Gabeleh (2013), by using the notion of P-property, it was proved that some late results about the existence and uniqueness of best proximity points can be obtained from the versions of associated existing results in the fixed point theory. Along the same line, in this paper, we prove that these results can be obtained under a weaker condition, namely, weak P-property.